1997
DOI: 10.1159/000239540
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interactions between Erythromycin, Clarithromycin, Roxithromycin and Phenytoin in the Rat

Abstract: The effects of the macrolide antibiotics, erythromycin, clarithromycin and roxithromycin, on the pharmacokinetic profile of phenytoin were studied in rats. Animals were injected with phenytoin (100 mg/kg, i.p.) daily for 4 days and then they were given phenytoin (20 mg/kg, i.p.) alone or the same dose of phenytoin together with erythromycin (50 mg/kg, i.p.), clarithromycin (50 mg/kg, i.p.) or roxithromycin (50 mg/kg, i.p.). In another set of experiments, the same protocol was followed except that erythromycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…In contrast to rifampicin, however, phenytoin is primarily metabolized by CYP enzymes and is particularly susceptible to inhibitory drug interactions [ 7 ]. A study in rats showed that clarithromycin increases phenytoin AUC and elimination half-life significantly [ 17 ]. On one hand, this may lead to increased phenytoin bioavailability in CYP-inhibited environments, on the other hand, phenytoin elimination kinetics may be difficult to predict, and adverse reactions may arise.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to rifampicin, however, phenytoin is primarily metabolized by CYP enzymes and is particularly susceptible to inhibitory drug interactions [ 7 ]. A study in rats showed that clarithromycin increases phenytoin AUC and elimination half-life significantly [ 17 ]. On one hand, this may lead to increased phenytoin bioavailability in CYP-inhibited environments, on the other hand, phenytoin elimination kinetics may be difficult to predict, and adverse reactions may arise.…”
Section: Discussionmentioning
confidence: 99%